Stock price reactions to share repurchase announcements in Germany: Evidence from a tax perspective - Tobias Pick; Deborah Schanz; Rainer Niemann (Arbeitskreis Quantitative Steuerlehre (arqus), 2009)
In this study we analyse stock price reactions to share buyback announcements from a tax perspective in Germany. To determine the influence of taxes on stock prices on the announcement day of share buybacks two different tax regimes - the corporate imputation system and the classical corporate tax system - are analysed. Taking the shareholder structure into account, we find evidence that the share price reaction on share repurchase announcements was significantly larger under the full imputation system than under the classical corporate tax system with shareholder relief. Furthermore, we find evidence for the substitution hypothesis and the dividend clientele effect: High dividend paying companies have smaller positive price reactions than non-or lower dividend paying companies.
Keywords: 330